Evaluating the impact of aerobic and resistance green exercises on the fitness, aerobic and intrinsic capacity of older individuals - Yıldırım Ayaz, Elif; Dinçer, Berna; Mete, Emel; Kaygusuz Benli, Reyhan; Cinbaz, Gülser; Karacan, Esra; Cankül, Ayşegül; Mesçi, Banu (Elsevier Ireland Ltd, 2024)
Objective: Our study determined the impact of 12-week aerobic exercise (AE) and aerobic + resistance exercises (AE + RE) within the green exercise concept, on senior fitness, aerobic capacity, and intrinsic capacity (IC). Methods: The study was a multicenter, randomized controlled study conducted at two senior living facilities with individuals aged 65 and above whose cardiorespiratory and musculoskeletal conditions are suitable for moderate exercise and who have normal cognition levels. Block randomization was applied to 96 participants in a ratio of 1:1:1 to be assigned to AE, AE + RE, and control (C) groups. Intervention groups received exercise sessions led by physiotherapists within the senior living facilitiy gardens, with a frequency of once a week for 50 min, for 12 weeks. Also, they were prescribed additional exercise sessions on two additional days of the week. At the commencement of the study and 12th week, shuttle walking test, senior fitness test (SFT), intrinsic capacity assessment (with Timed Up and Go test, Mini Mental State Examination, Geriatric Depression Scale-15, Mini Nutritional Assessment, handgrip strength test) was conducted of all participants. The primary outcome was the Z score of IC, secondary outcomes were VO2max and SFT subparameters. The study was registered in the Protocol Registry and Results System (Clinicaltrials.gov PRS) with the registration number NCT05958745. Results: 90 participants successfully completed the study, with 30 individuals in each of the AE, AE + RE, and C groups. By the end of the 12th week, the arm curl score was significantly higher in the AE + RE compared to the C (mean difference: 3.96, 95 % CI= 2.47 to 5.46, p = 0.01). There were significant differences in chair stand, two-minute step, 8-foot up-and-go, chair sit and reach, and back scratch tests in both AE and AE + RE compared to C. AE and AE + RE exhibited significantly higher shuttle test distances and VO2max values compared to the C (p < 0.0001). AE + RE achieved a significantly higher total IC score than the C (mean difference: 0.59, %95 CI= -0.07 to 1.26, p = 0.025). Conclusion: In this study within the green exercise concept, both AE and AE + RE led to similar improvements in strength, flexibility, mobility, endurance, and aerobic capacity. Notably, AE + RE demonstrated an additional benefit by increasing the total IC, while AE alone did not exhibit the same effect.
Keywords: Aerobic Capacity; Green Exercise; Intrinsic Capacity; Older Individuals; Senior Fitness